The civilizational role of Islam in the Indian subcontinent: The Delhi sultanate - Islam, Arshad (IIUM Press, 2017)
Muslim presence was manifest in the coastal regions of Southern India from the earliest days of Islam, as evidenced by the establishment of Arab trading settlements, with minor political impact prior to the conquests in Northern India from the beginning of the 8th century, which solidified the influence of Islam leading to tangible political and socio-cultural impacts in the region. The history of India furnishes an amazing picture of the syntheses of many divergent cultural trends which were gradually transformed by a process of mutual adjustment and assimilation. Islam played a significant role in this by contributing to India’s multi-cultural and multi-religious ethos, embedding the subcontinent in the Arab-Islamic maritime civilization, stretching from southern Africa to China, particularly in connecting Africa as well as the great Turkic empires of Central Asia. It offers a pertinent example of the interaction of human minds and the effects of cultural and civilizational contacts on indigenous customs, religion, literature and arts. This paper examines the impact of Islam in the Indian Peninsula from three different angles: its political predominance, its intellectual and cultural impact, and finally, its influence on art and architecture. Based mainly on Arabic and Persian sources, the article focuses on the intellectual legacy, achievements and the role that the Indian Muslims played in the Indian subcontinent during the Delhi Sultanate, the first major Islamic political authority to govern large parts of South Asia.